2010
DOI: 10.1017/s0007114510003533
|View full text |Cite
|
Sign up to set email alerts
|

Maternal consumption of high-prebiotic fibre or -protein diets during pregnancy and lactation differentially influences satiety hormones and expression of genes involved in glucose and lipid metabolism in offspring in rats

Abstract: Risk of developing the metabolic syndrome may be influenced by nutritional environment early in life. We examined the effects of high-fibre (HF) and high-protein (HP) diets consumed during pregnancy and lactation on satiety hormones and expression of genes involved in glucose and lipid metabolism in offspring. Wistar dams were fed a control (C), HF or HP diets during pregnancy and lactation. At parturition, litters were culled to ten pups. At 21 d, all pups were weaned onto C diet. At 7, 14, 21, 28 and 35 d af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 46 publications
2
42
1
Order By: Relevance
“…The present results are consistent with earlier data on adult rats fed with fibre-enriched diets (18 -20) , and with the study in rat pups born from dams fed a high-fibre diet (21) . Such a trophic effect on the offspring's colon suggests that the intestinal microbiota was affected in pups.…”
Section: Discussionsupporting
confidence: 93%
“…The present results are consistent with earlier data on adult rats fed with fibre-enriched diets (18 -20) , and with the study in rat pups born from dams fed a high-fibre diet (21) . Such a trophic effect on the offspring's colon suggests that the intestinal microbiota was affected in pups.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that maternal high-protein diet did not affect litter mass, litter size or sex ratio in the voles. No effects on reproductive output by maternal dietary protein content were also found in laboratory mice and rats (Derrickson and Lowas, 2007;Hallam and Reimer, 2013;Maurer and Reimer, 2011). However, results have not been unequivocal.…”
Section: Discussionmentioning
confidence: 90%
“…Laboratory studies suggest that low maternal protein intake during gestation and/or lactation can result in offspring with lower birth mass, reduced growth rate and higher blood pressure in adulthood (Derrickson and Lowas, 2007;Passos et al, 2000;Zambrano et al, 2006). In contrast, maternal high-protein diet can induce increased growth and improve glucose homeostasis (Maurer and Reimer, 2011;Thone-Reineke et al, 2006). However, other studies found that maternal low-protein diet increased abdominal fat deposition in mice (Han et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, a high protein intake in rats during pregnancy and lactation also results in male offspring with higher blood pressure and female offspring with higher body mass and increased fat pad mass; it is possible to speculate that these effects are also mediated by epigenetic mechanisms (36) . Maurer & Reimer (37) showed that a maternal highprotein diet, but not high-prebiotic fibre diet, during pregnancy and lactation could negatively influence the expression of genes involved in glucose and lipid metabolism in the offspring rats. These early changes, perhaps based on epigenetic mechanisms, could have long-term consequences for the development of obesity and the metabolic syndrome (37) .…”
Section: Epigenetic Mechanisms Elicited By Maternal Diet During Pregnmentioning
confidence: 99%
“…Maurer & Reimer (37) showed that a maternal highprotein diet, but not high-prebiotic fibre diet, during pregnancy and lactation could negatively influence the expression of genes involved in glucose and lipid metabolism in the offspring rats. These early changes, perhaps based on epigenetic mechanisms, could have long-term consequences for the development of obesity and the metabolic syndrome (37) . Interestingly, a number of clinical studies have shown that the highest risk for development of the metabolic syndrome and diabetes occurs in adults who are born small for gestational age and become overweight in early childhood.…”
Section: Epigenetic Mechanisms Elicited By Maternal Diet During Pregnmentioning
confidence: 99%